Necesidad de reformar el art. 59 de la ley orgánica del sistema nacional de contratación pública, en relación a la contratación de bienes muebles e inmuebles. - Aguirre Valdivieso, Gonzalo Iván (2015)
The Article 59 of the Organic Law of the National System of Public Procurement allows the leasing of real estate, subject to the provisions of the regulations and the Act, but does not indicate the type or the circumstances in which this will take place types of contracts. It also does not indicate anything about the lease of goods, so it is not indicated the nature of the lease of goods, standardization and where should proceed to property lease. The activity of the government or the exercise of administrative function is expressed in primary defined legal categories: a) The regulations or administrative provisions; b) The decisions or administrative acts, and c) administrative contracts. The type of real estate leasing is normalized in the Regulation to the Law of the National System of Public Procurement, but this is illegal because a regulation should not be above the law, the regulation does not rule, but provides breaks of how to carry out, for which the mode of this type of contract must be included in the Organic Law of the National System of Public Procurement. Because of the circumstances listed in the General Regulations reason the Organic Law of the National System of Public Procurement regulates the leasing of real estate and the Organic Law of the National System of Public Procurement no, then goes against the foundation of the right goal for which rights and duties is developed, creating legal uncertainty of public institutions.